Numerical Analysis Method considering Coupled Effects of THMC Multifields on Unsaturated Expansive Soil Subgrade Treated with Lime - Jie Liu; Pan Chen; Zheng Lu; Hailin Yao (Geofluids)
The response model subjected to coupled effect of thermo-hydro-mechano-chemical (THMC) was built in the context of basic theories in the polyporous polyphasic medium mechanics, the mixture theory in the continuum mechanics, and the thermodynamic theories. The finite element discretization of the response model was implemented based on the Galerkin method. The processes of salt leaching and accumulating were analyzed in the numerical results. The results among the numerical results and measured results were compared and discussed. Finally, the solutes migration rule of the soil subjected to the atmosphere eluviations was revealed, and the reasonableness of the coupling model and the finite element method was proved. The agreement between the numerical and the measured results was good, which indicates that the THMC model and finite element program were useful in solving the coupling problems of unsaturated soil. Moreover, the salt dissolution process has a larger effect on the salt movement compared to that of the salt accumulation process. Comparing with the salt leaching effect caused by rainfall, the salt accumulation effect caused by evaporation was smaller.